Experimental Study of Thermal Behavior of a Single-phase Natural Circulation Loop with Vertical Heater and Cooler. Issue 1 (June 2021) - Hariyanto, D; Permana, S
Abstract: The natural circulation systems have been widely applied to various technologies, for example, safety systems in molten salt reactors. Hence the instability of the natural circulation system became an exciting topic to study. This study aimed to find out the effect of horizontal width variation on the thermal behavior of a single-phase natural circulation loop (NCL) with vertical heater and vertical cooler. Three loops with horizontal widths of 50 cm, 100 cm, and 150 cm, respectively, were designed for experimental studies. Meanwhile, the vertical height of all three loops was 100 cm. The cooler was installed vertically on the upper arm of the loop to cool the fluid. The heater was installed vertically on the forearm on the other side of the loop to heat the fluid. K-type thermocouples integrated with the data acquisition system were used to measure the temperature distribution in several zones of the loop directly. The conclusion obtained in this study was a single-phase natural circulation loop with vertical heater and vertical cooler did not indicate a reversal of the direction of heat transfer at each operating power and geometry configuration. This study is expected to be one of the references to the design of a single-phase natural circulation loop as an advanced nuclear reactor passive safety system.